(untitled) (Global Journal of Management and Business Research, 2018)
The study was set out to determine road user charges (per/km). It carried out survey on different vehicle classifications (category) according to their average weights and converted them to an equivalent standard axle load (ESAL). This was utilized to determine the charges payable, the annual average daily traffic (AADT) and the cost component of a federal highway in the South-Eastern Nigeria on a yearly basis. The various needed data is collected especially the AADT. The charge per ESAL was obtained by dividing the annual roadway costs by aggregating the total number of the ESAL-Km it incurs on the 80.5km Onitsha-Owerri highway in a year. Furthermore, charge per vehicle was obtained by multiplying the individual ESALs by the charge per ESAL-Km. The study results show that road user charges (RUC) are directly proportional to the equivalent standard axle load (ESAL). This means that higher charges are paid by road users that cause more unit wear to the road. Hence the results: Tricycles and light passenger vehicle charges are negligible, Minibuses to pay #x20A6;0.98/km, Trucks and Buses to pay #x20A6;11.6/km, vehicles with multi-axles to pay #x20A6;17/km, and Heavy Construction Machinery and Earth Moving Equipment to pay #x20A6;41.59/km to recover the #x20A6;517 million computed as the annual roadway cost. Road user charges must serve the essential function of rationing the available supply among many possible demands.